Superbenzene–Porphyrin Gas‐Phase Architectures Derived from Intermolecular Dispersion Interactions. Issue 59 (17th October 2018) - Lungerich, Dominik; Hitzenberger, Jakob F.; Hampel, Frank; Drewello, Thomas; Jux, Norbert
Abstract: A systematic series of superbenzene–porphyrin conjugates was synthesized and characterized. All conjugates show a high degree of cluster formation that correlates to the amount of tert‐ butylated hexa‐ peri ‐hexabenzocoronenes ( t BuHBCs) attached to the porphyrin's periphery. Determined by mass spectrometry and X‐ray diffraction, van der Waals (vdW) interactions like London dispersions (LD), stemming from solubilizing tert‐ butyl groups, were identified to be the major reason for the cluster formation. Cluster sizes comprised of more than twenty molecules with masses up to 70 000 Da were observed, which are rare examples of large architectures based on synthetic functional molecules, assembled by dispersion interactions. Novel strategies towards the design of solution processable functional materials, capable of dynamic transformations based on non‐covalent synthesis can be envisioned. Abstract : Superbenzene‐porphyrin conjugates were synthesized that show a high cluster formation ability. The cluster size correlates to the amount of tert ‐butylated hexa‐ peri ‐hexabenzo‐coronenes attached to the porphyrin's periphery. Determined by mass spectrometry and X‐ray diffraction, London dispersion interactions stemming from the tert ‐butyl groups were identified to be the major reason for the cluster formation.